2022
DOI: 10.1155/2022/9275801
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bronchopneumonia Inpatients’ Total Hospitalization Expenses Based on BP Neural Network and Support Vector Machine Models

Abstract: Objective. BP neural network (BPNN) model and support vector machine (SVM) model were used to predict the total hospitalization expenses of patients with bronchopneumonia. Methods. A total of 355 patients with bronchopneumonia from January 2018 to December 2020 were collected and sorted out. The data set was randomly divided into a training set ( n = 249 ) and a test set ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Due to the skewed distribution of hospitalization costs for colorectal cancer patients, traditional linear regression models have limitations in the study of factors influencing hospitalization costs. The studies have shown that ( 14 , 22 ) RF algorithm and SVR algorithm are more suitable for the prediction of hospital costs as compared to other algorithms. And no study has compared RF algorithms to SVR algorithms in the prediction of the cost of hospitalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the skewed distribution of hospitalization costs for colorectal cancer patients, traditional linear regression models have limitations in the study of factors influencing hospitalization costs. The studies have shown that ( 14 , 22 ) RF algorithm and SVR algorithm are more suitable for the prediction of hospital costs as compared to other algorithms. And no study has compared RF algorithms to SVR algorithms in the prediction of the cost of hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the RF algorithm and SVR algorithm were selected in this study for modeling and comparative. Some research shows that machine learning approaches are more applicable to the study of big data in healthcare, and other studies have shown that SVR models have a strong generalization ability in hospitalization cost prediction compared to other machine learning algorithms ( 22 ). Therefore, this study introduces support vector regression(SVR) models to explore the factors influencing hospitalization costs.…”
Section: Methodsmentioning
confidence: 99%
“…It also effectively avoids the shortcomings of traditional statistical theory that quickly make the model fall into the local minimum due to overfitting and too many dimensions. Its progressive nature makes statistical theory develop rapidly under the efforts of many researchers [ 14 , 15 ].…”
Section: The Concept Of Support Vector Machinementioning
confidence: 99%